Peningkatan Hasil Belajar IPS Siswa Menggunakan Model Think Pair Share di Kelas V SD - Edo Ferdiansyah; Hamimah Hamimah; Rahmatina Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The purpose of this study was to describe an increase in student learning outcomes in science learning using the Cooperative Think Pair Share model. This research is a classroom action research (PTK), using a qualitative and quantitative approach. The results showed an increase in: (a) Learning Planning in the first cycle obtained an average of 71.25% (C) increased in the second cycle to 90% (SB), (b) Learning Implementation aspects of the teacher the first cycle obtained an average the average is 76.38% (C) increased in the second cycle to 91,66% (SB) and the Learning Implementation aspects of the first cycle students get an average of 76,38% (C) increased in the second cycle to 91,66% (SB), (c) Learning outcomes of students in cycle I obtained an average of 76.65 (C) increased in the second cycle to 84.06 (B). From the results of the study it can be concluded that the Cooperative Type Think Pair Share model improves the science learning outcomes of the fifth grade students of 25 Gadut Elementary School Tilatang Kamang.Keywords : learning outcomes, Think Pair Share models